The Great Conversation. A Discussion on Peace after the First World War - Bouchard, Carl (Peacemaking and International Order after the First World War, 2023)
The Great Conversation was a broad-based discussion on international issues and world peace that took place beyond the traditional circles of power and of the intellectual elite at the end of the Great War. In a time of global destabilisation and political innovations, it gave ordinary men and women, mainly in Western countries, the opportunity, the desire and the legitimacy to take a stand on international issues by virtue of a new interpretation of their political rights and their own agency. It was an unprecedented, unorganised, yet transnational movement of thought, which questioned the meaning of citizenship in a context of democratisation of political life.